CONCEPTION OF MENTAL PATHOLOGY AT ALIVE THE BEMBE PEOPLE IN THE TOWN OF KISANGANI - WACIBA , William WILONDJA; Norbert NONGO MASUMBUKO (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
This studytry to know the conception that the Bembe people having left its traditional medium (because of the disasters, especially), and currently residing in the town of Kisangani during more than two decades, is made mental pathology. It is thus a question of seeing whether the urbanistic and scientific influence would have changed its traditional conception (mystical conception) in front of the mental illness. Thus we managed a questionnaire with a sample with choices reasoned composed of 50 inquired born and grown in their socio-cultural medium. With the exit of our research, we noted thatthe conception that the Bembe people of the Kisangani town preaches to explain, to treat and to prevent themental illnessremains mystical order (magico-religious) in the large majority of these people, that notwithstanding the scientific, urbanistic influence(modernity).